2019
DOI: 10.18203/2394-6040.ijcmph20194519
|View full text |Cite
|
Sign up to set email alerts
|

Study of contraceptive use in married women of reproductive age group in urban slum area of western Maharashtra

Abstract: Background: India is world’s second most populous country next to China. Family planning is a key intervention for population control. In urban field, most of population (60%) resides in urban slum area with deprived and vulnerable population. This study was conducted to determine the prevalence of contraceptive use in married women of reproductive age group also to study socio-demographic factors and sources associated with the contraceptive use and the reasons behind not using.Methods: A community based desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…A similar study conducted by Kasa et al, among women in resource limited area of Ethiopia corroborates our findings ( 18 ). Also, findings from the study conducted by Mitkari et al ( 19 ), as well as that conducted by Adeyemi et al ( 14 ), are in keeping with our results. Hence, there is a need to improve contraceptive literacy in rural communities of Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…A similar study conducted by Kasa et al, among women in resource limited area of Ethiopia corroborates our findings ( 18 ). Also, findings from the study conducted by Mitkari et al ( 19 ), as well as that conducted by Adeyemi et al ( 14 ), are in keeping with our results. Hence, there is a need to improve contraceptive literacy in rural communities of Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…A signi icant association between contraceptive acceptance and type of family, socio-economic status and education was observed in a study conducted among women of reproductive age in rural Maharashtra. (Mitkari et al, 2019) Similar indings have been reported by other Indian studies. (Makade et al, 2012;Mozumdar et al, 2019)…”
Section: Discussionsupporting
confidence: 87%
“…37 Other studies also showed that women educational status and contraceptive knowledge were factors influencing contraceptive uptake. 18,27,38 There is, therefore, the need to improve contraceptive literacy in rural communities of Nigeria especially the north central. This will involve an increased and sustained political will by the Nigerian government and its partner agencies to invest more on contraceptive use education programmes to improve the knowledge-base of rural women regarding contraception.…”
Section: Discussionmentioning
confidence: 99%